HUMAN RIGHTS PROTECTION FOR INDONESIAN MIGRANT WORKERS: CHALLENGES FOR ASEAN - Win Sherly Tan; Rina Shahriyani Shahrullah (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThe AEC is good news for Indonesian migrant workers wanting to work overseas. Unfortunately, many Indonesian migrant workers have been deported from ASEAN countries because of having problems. This study adopts the normative legal research method. It argues that AICHR may be slow in resolving the problems of human rights. It is also argued that the ASEAN Committee on Migrant Workers works in the absence of the political commitment of ASEAN leaders to implement the Cebu Declaration. Therefore, the best solution is public participation in the ASEAN countries to protect migrant workers.IntisariKomunitas Masyarakat Ekonomi ASEAN adalah berita baik untuk Tenaga Kerja Indonesia (TKI) untuk bekerja di luar negeri. Namun, banyak TKI yang kembali dari negara-negara ASEAN dikarenakan mendapatkan berbagai permasalahan. Penelitian ini mengadopsi jenis penelitian hukum normatif. Penelitian ini menyimpulkan bahwa AICHR lamban dalam menyelesaikan permaslahan tentang hak asasi manusia. Penelitian ini juga menyimpulkan bahwa komunitas ASEAN tentang Pekerja Migran bekerja dengan tidak adanya komitmen politik dari para pemimpim ASEAN dalam menerapkan Deklarasi Cebu. Oleh sebab itu, dibutuhkan partisipasi ASEAN dalam melindungi TKI.